Optimization of Ultrasonic and Microbubble Disinfection for Escherichia coli and Staphylococcus aureus: Experimental Design and Effectiveness Evaluation - Pitjamit, Siwasit; Vichiansan, Norrapon; Leksakul, Komgrit; Boonyawan, Dheerawan (Journal of Engineering and Technological Sciences, 2024)
This study investigated the synergistic application of ultrasonic (UL) and microbubble (MB) technologies for the disinfection of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Optimal conditions for both techniques were determined through a comprehensive experimental design, resulting in an effective disinfection rate of 100% as assessed by the ten-fold dilution spread plate count method. The study evaluated three key parameters of the UL/MB system, i.e., UL duration time, MB duration time, and gas flow rate within the ranges of 30-60 sec, 30-60 sec, and 15-30 ml/min, respectively. A 2k full factorial design with three replications, five center points, and blocking was employed for robust statistical analysis. Based on the empirical data and rigorous statistical examination, the optimal conditions for achieving sterilization of E. coli and S. aureus were determined as 30 sec UL duration, 30 sec MB duration, and 30 ml/min gas flow rate; and 60 sec UL duration, 60 sec MB duration, and 15 ml/min gas flow rate, respectively. Utilizing these optimal conditions, the disinfection efficacy was assessed, revealing an inhibition rate of 54% for E. coli and an inhibition rate of 19% for S. aureus, with consistent improvement observed across the three replication trials. These findings underscore the potential of UL/MB technology as an effective disinfection strategy against common bacterial pathogens